Common Cycles in Volatility and Cross Section of Stock Returns - Jozef Barunik; Lucie Kraicova (Charles University in Prague, Institute of Economic Studies (IES), 2017)
We study the relationship between conditional quantiles of returns and the long-, medium- and short-term volatility in a portfolio of financial assets. We argue that the combination of quantile panel regression and wavelet decomposition of the volatility time series provides us with new insights into the pricing of risk and increases the accuracy of our estimates of re-turn quantiles. Our results contribute to the literature on the risk-return relationship with an emphasis on portfolio management under various investment horizons. Moreover, the analytical framework that we introduce should be applicable to a wide range of problems outside of our research area.
Keywords: C14; C21; C58; G17; 330; Return predictability; Quantiles; Wavelets; Panel data